miR-129-5p Promotes Osteogenic Differentiation of BMSCs and Bone Regeneration via Repressing Dkk3 - Changming Zhao; Yulin Gu; Yan Wang; Qiaozhen Qin; Ting Wang; Meng Huang; Heyang Zhang; Yannv Qu; Jingwen Zhang; Zhangzhen Du; Xiao-Xia Jiang; Lulu Xu (Hindawi Limited, 2021)
Objective. Accumulating evidence indicates that microRNAs (miRNAs) play crucial roles in osteogenic differentiation. However, the associated mechanisms remain elusive. This paper is aimed at exploring the role of miR-129-5p in regulating bone marrow mesenchymal stem cell (BMSC) differentiation and bone regeneration in vivo and in vitro. Methods. BMSCs were transduced by miR-129-5p mimic, miR-129-5p inhibitor, and negative control lentivirus. The ability of BMSC differentiation to osteoblast was tested by alkaline phosphatase (ALP) and alizarin red staining (ARS). The expression of osteogenic genes (Runx2, Bmp2, and OCN) was examined via quantitative RT-PCR and western blot. A mouse model of calvaria defect was investigated by Micro-CT, immunohistochemistry, and histological examination. The luciferase reporter gene assay was performed to confirm the binding between Dkk3 and miR-129-5p. For the transfection experiments, lipofectamine 3000 was used to transfect pcDNA-Dkk3 into BMSCs to overexpress Dkk3. Coimmunoprecipitation and immunofluorescent localization assay were included for exploring the role of Dkk3 and β-catenin. Results. miR-129-5p was induced in BMSCs and MSC cell line C3H10T1/2 cells under osteogenic medium. Overexpression of miR-129-5p significantly promoted osteogenic differentiation of BMSCs in vitro. Moreover, BMSCs transduced with miR-129-5p mimic exhibited better bone regeneration compared with BMSCs transduced with control counterpart in vivo. Luciferase and western blot data showed that Dickkopf3 (Dkk3) is a target gene of miR-129-5p and the expression of Dkk3 was inhibited in BMSCs transduced with miR-129-5p mimic but enhanced in BMSCs transduced with miR-129-5p inhibitor. In addition, Dkk3 interacted with β-catenin directly. Conclusions. miR-129-5p promotes osteogenic differentiation of BMSCs and bone regeneration, and miR-129-5p/Dkk3 axis may be new potential targets for the treatment of bone defect and bone loss.